2009
DOI: 10.2298/vetgl0902029b
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological effects of chronic exposure to lead on kidneys of brown trout (Salmo trutta m. Fario)

Abstract: The aim of the present study was to investigate the histopathological changes on the kidneys of the brown trout (Salmo trutta m. Fario) inflicted by per os lead poisoning in the 46-week experimental period. The fish were kept in well-oxygenated freshwater basins. Approximately calculated toxic doses of lead-acetate for fish were 550 mg/kg. Following the experimental period, fish organs, in particular kidneys, were examined by light microscopy. Only fish with lesions observed in kidneys were further examined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
2
9
0
1
Order By: Relevance
“…The changes in the gills in our study were clear in case of fish group exposed to cadmium and were characterized by hyperplasia of gill filaments, congestion and eosinophilic granular cells infiltration; the results were go parallel with the findings of Besirovic et al (2010). The changes in the gills were also noticed in the treated group; however it is not indicative to inefficiency of the clays to inhibit the toxicity but it may attributed to failure of the tissue to regenerate the chronic changes that noticed in branchial tissue.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The changes in the gills in our study were clear in case of fish group exposed to cadmium and were characterized by hyperplasia of gill filaments, congestion and eosinophilic granular cells infiltration; the results were go parallel with the findings of Besirovic et al (2010). The changes in the gills were also noticed in the treated group; however it is not indicative to inefficiency of the clays to inhibit the toxicity but it may attributed to failure of the tissue to regenerate the chronic changes that noticed in branchial tissue.…”
Section: Discussionsupporting
confidence: 90%
“…Heavy metals can affect aquatic organisms through water, sediment or food chain (Zyadah, 1995). Cadmium (Cd) is an important inorganic toxicant widely distributed in the environment because of its various industrial uses and it is a nonessential element to all living organisms (Randi et al, 1996;Besirovic et al, 2010). Also contamination of groundwater from smelting and industrial uses as well as the use of sewage sludge as a food-crop fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…The higher bioaccumulation of Zn in kidney contributes substantially to injury, probably due to distal tubules deposition (Woodling et al 2001). The increase of zinc resorption in tubules can cause changes related to osmotic nephrosis and convoluted proximal tubules become hypertrophic and hyperplastic (Besirovic et al, 2010). The dose sufficient to cause osmotic-type nephroses also increases frequency and a degree of lesions related to chronic progressive nephropathies (Haschek et al, 2002).…”
Section: Histopathology Of Liver and Kidneymentioning
confidence: 99%
“…It is known that not all metals taken up by organisms are bioaccumulated; fish can, to a certain degree, regulate metal concentration in tissues (Maceda-Veiga et al, 2012;Pourang et al, 2005), but Cd is one of the most toxic metals, as it is nonessential, and can quickly bioaccumulate in fish (Liu et al, 2011). Even though metallothioneins tend to detoxify nonessential elements (Hansen et al, 2007), their excretion is a slow process (Besirovic et al, 2010). Accordingly, a previous study by Calza et al (2004) also demonstrated the absence of Cd accumulation in G. brasiliensis tissues.…”
Section: G Brasiliensis May Be Able To Decrease the Residual Time Ofmentioning
confidence: 99%